The Relationship Between Mental Health and Quality of Life of Hemodialysis Patients Referred to Hospitals Affiliated to Shiraz University of Medical Sciences - F. Sharif; F. Vedad (Iran University of Medical Sciences, 2007)
Background & Aim: Although hemodialysis is one of the most useful and modern treatment methods for patients with chronic renal diseases, there has not been considerable achievement in understanding and treating physical and psychosocial problems of these patients. Decrease in mental health status of hemodialysis patients affects their quality of life and may produce performance disorder. The purpose of this study was to investigate the relationship between mental health and quality of life of hemodialysis patients referred to hospitals affiliated to Shiraz University of Medical Sciences.   Material & Method: Ninety patients were selected through convenient sampling and data was collected by a demographic questionnaire, General Health Questionnaire, and Short form quality of life questionnaire (SF-36). Mental health was assessed in four domains: somatoform symptoms, anxiety, social dysfunction and depression. The SF-36 questionnaire is summed into eight scales of health: physical function, social function, limitation in role due to emotional problem, mental Health, vitality, bodily pain, and general health. The data were analyzed using t-test, spearman's correlation, and Anova.   Results: The results revealed that most domains in quality of life were correlated with mental health domains. General health perception and physical function domains were correlated significantly with three domains of mental health: anxiety, social function and depression (p<0.012, 0.p<0.001,p< 0.004 ). Somatoform symptoms were correlated significantly with mental health domain of quality of life (p<0.02). Finally, social function was correlated significantly with social dysfunction domain of life quality (p<0.05). Also, anxiety and somatoform domains of mental health had more significantly relationship in women than men (p= 0.006 and p= 0.25, respectively). Of quality of life domains, physical function had more significantly relationship in men than women (p=0.03) and bodily pain had more significantly relationship in women than men (p= 0.006).   Conclusion: The result of this study indicated that many quality of life domains were correlated with mental health domains and hemodialysis had effect on different aspects of patient's life. The results also indicated that such demographic characteristic as age, gender, marital status, other diseases and length of hemodialysis treatment had relationship with some aspects of life quality and mental health.